PENGARUH FASILITAS DAN KUALITAS LAYANAN TERHADAP KEPUASAN ANGGOTA (SETUDI KASUS PADA KOSPIN MULTI DANA SEMARANG) - Rangga Ikrar Putranto, 10.05.51.0150 (Students Journal of Economic and Management, 2013)
Research by title EFFECT OF FACILITIES AND QUALITY SERVICE SATISFACTION OF MEMBERS CASE STUDY ON KOSPIN MULTI DANA SEMARANG a study to determine and analyze whether the variable variable facilities and services provided by Kospin Multi Dana Cabang Semarang significant effect on member satisfaction Kospin Multi Dana cabang Semarang. Therefore, the authors take the title âEFFECT OF FACILITIES AND QUALITY SERVICE SATISFACTION OF MEMBERS (CASE STUDY ON KOSPIN MULTI DANA SEMARANG) â. The samples used in this study were 100 responden.Teknik used in this study used purposive sampling to select respondents or according to the requirements to become a respondent has been a member for at least 1 year and at least 17 ââyears of age. The collected data is tested first by using test validity and reliability in order to obtain valid and reliable results that can be used in subsequent testing. Of the test result that is stronger than the facility variable variable service because, comfort members while performing activities of savings and loans in Kospin Multi Dana more highlighted by the members Kospin Multi Dana. his study has limitations that the variables used only in the dimension of facilities and quality of service, while there are many other factors which may affect the satisfaction of a member. Therefore, further research is suggested to consider other variables that have not been present in the sample penelitianini lebihluas and determination. Keywords : Facilities, quality of service, member satisfaction